The Presumption of Innocence and Investigative Procedures: Examining Normative Disparity through the Lens of Islamic Epistemology - Pujiono; Muslim Fikri; Moh. Roqib (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the tension between the presumption of innocence and investigative practices within criminal justice systems from the perspective of legal philosophy and Islamic epistemology. Employing a qualitative library research design, the study analyzes classical and contemporary legal texts to explore the relationship between ontological legal principles and epistemological processes in investigations. The findings reveal that the presumption of innocence should be understood as an ontological commitment that defines individuals as non-culpable legal subjects. However, in practice, investigative procedures often operate in a confirmatory mode, prioritizing suspicion and validation of initial assumptions rather than objective verification. This creates a structural misalignment between the ontological foundation of criminal law and the epistemological orientation of investigative practices. As a consequence, epistemic injustice emerges, where suspects are marginalized and denied meaningful participation in the construction of legal truth. From the perspective of Islamic epistemology, which emphasizes certainty (yaq?n), restraint, and moral accountability, such practices contradict the principles of substantive justice. The study proposes the need for reconstructing investigative epistemology by repositioning the presumption of innocence as an operative guiding principle. By integrating philosophy of law, epistemic justice, and Islamic legal theory, this research contributes to contemporary legal scholarship by offering a normatively coherent framework for achieving procedural fairness and substantive justice across legal systems.